2012
DOI: 10.1111/j.1748-5991.2012.01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory policy outputs and impacts: Exploring a complex relationship

Abstract: In this article, we pursue the objective of empirically testing the extent to which changes in environmental policy outputs can explain changes in environmental impacts. Previously, systematic testing of this relationship was hampered by the lack of a compelling measurement of changes in regulatory policy outputs. To remedy this, we present a novel approach to the measurement of events of regulatory output change. We illustrate our concept by employing data on changes in clean air regulations in 24 advanced de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
152
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 48 publications
2
152
0
1
Order By: Relevance
“…In addition, measures of density and intensity associated with policy instruments have been put forward (Schaffrin et al 2015). The former equals the sum of the number of policy instruments in a specific domain; the latter is about their specific content (Knill et al 2012) and is associated with the importance or significance of the particular policy intervention. 4 Since the discussion on 'indexes' of policy change is, however, centered on components and instruments, datasets are created specifically for each specific policy area.…”
Section: Methodological Steps For Constructing An Index Of Disproportmentioning
confidence: 99%
“…In addition, measures of density and intensity associated with policy instruments have been put forward (Schaffrin et al 2015). The former equals the sum of the number of policy instruments in a specific domain; the latter is about their specific content (Knill et al 2012) and is associated with the importance or significance of the particular policy intervention. 4 Since the discussion on 'indexes' of policy change is, however, centered on components and instruments, datasets are created specifically for each specific policy area.…”
Section: Methodological Steps For Constructing An Index Of Disproportmentioning
confidence: 99%
“…The third level corresponds to the concrete setting or calibration of particular policy instruments. Knill, Schulze, and Tosun (2012) added a fourth category which denotes the scope of a policy instrument, that is, how it governs its target groups. These four categories have been used to empirically assess how policies -in terms of their density and intensity -have expanded and/ or contracted over time (Bauer, Green-Pedersen, Héritier, & Jordan, 2012;Jordan, Bauer, & Green-Pedersen, 2013;Knill et al, 2012;Schaffrin, Sewerin, & Seubert, 2014).…”
Section: Disproportionate Climate Policy Responses: Some Empirical Chmentioning
confidence: 99%
“…Teixidó-Figueras et al [50] consider urbanization as one of the factors which create global environmental inequality because of activities requiring more resources. Knill et al [51] found that rapid urbanization can increase NO X emission in OECD countries. According to Lung et al [52], the high-speed urbanization trend in Asia is an important factor in the production of air pollution due to traffic jams and increased energy consumption, which leads to inequality among people with different socio-economic levels.…”
Section: Urban Development Disparity and No X Emissionmentioning
confidence: 99%